2017
DOI: 10.2147/dddt.s136150
|View full text |Cite
|
Sign up to set email alerts
|

An in silico high-throughput screen identifies potential selective inhibitors for the non-receptor tyrosine kinase Pyk2

Abstract: The non-receptor tyrosine kinase proline-rich tyrosine kinase 2 (Pyk2) is a critical mediator of signaling from cell surface growth factor and adhesion receptors to cell migration, proliferation, and survival. Emerging evidence indicates that signaling by Pyk2 regulates hematopoietic cell response, bone density, neuronal degeneration, angiogenesis, and cancer. These physiological and pathological roles of Pyk2 warrant it as a valuable therapeutic target for invasive cancers, osteoporosis, Alzheimer’s disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Increasing evidence has demonstrated that FAK/Pyk2 signaling regulates hematopoietic cell differentiation, bone mass formation, neuronal degeneration, inflammatory response and cancer. Therefore, Pyk2 is a valuable therapeutic target for inflammatory diseases and malignancies [ 80 , 81 ]. Based on protein structure, targeting tyrosine kinases has focused on the ATP binding pocket to inhibit catalytic activity and repress the pathways involved in carcinogenesis, EMT and metastasis.…”
Section: Pyk2 and Cancersmentioning
confidence: 99%
“…Increasing evidence has demonstrated that FAK/Pyk2 signaling regulates hematopoietic cell differentiation, bone mass formation, neuronal degeneration, inflammatory response and cancer. Therefore, Pyk2 is a valuable therapeutic target for inflammatory diseases and malignancies [ 80 , 81 ]. Based on protein structure, targeting tyrosine kinases has focused on the ATP binding pocket to inhibit catalytic activity and repress the pathways involved in carcinogenesis, EMT and metastasis.…”
Section: Pyk2 and Cancersmentioning
confidence: 99%
“…In SBVS, tuned datasets should be used to identify the protocol, conformational sampling, and/or scoring methods that induces the best enrichment in active compounds (Allen et al, 2015 , 2017 ; Lacroix et al, 2016 ; Li et al, 2016 ; Nunes et al, 2016 ; Meirson et al, 2017 ). For instance, Allen et al ( 2015 , 2017 ) evaluated different scoring schemes using DUD-E generated decoys and successfully identified dual EFGR/BRD4 inhibitors.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…An automated tool was made available online to generate decoys from user-supplied ligands using the same protocol ( http://decoys.docking.org ). The possibility to generate decoy sets for any target has been revealed successful and is now widely used by the scientific community (Lacroix et al, 2016 ; Nunes et al, 2016 ; Allen et al, 2017 ; Meirson et al, 2017 ).…”
Section: Selected Databasesmentioning
confidence: 99%
“…The potential of PYK2 in tumor therapy is attracting more attentions due to recent development of PYK2 inhibitors. 38 , 39 Several PYK2 inhibitors had been reported to exert tumor-suppressing role in bone tumors and breast cancer. 40 42 For example, the PF-562,271 is a potent, ATP-competitive, reversible inhibitor of PYK2.…”
Section: Discussionmentioning
confidence: 99%